ANALISA PEMANFAATAN APLIKASI KEUANGAN ONLINE SEBAGAI MEDIA UNTUK MENGELOLA ATAU MEMANAJEMEN KEUANGAN - Yuni Fitriani (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2021)
Abstract: The existence of information technology provides many benefits in many aspects of life, especially if we are able to maximize the use of such technology, one of which is the emergence of online financial management applications as a medium to manage or manage finance both personal and business finance. This online financial application makes it very easy to plan budgets and record expenses as well as to make financial statements. In this study, online financial applications include financial applications that help manage personal or individual finances, families as well as businesses such as online financial applications Bukukas, BukuWarung, Keuanganku and Money Lover. The research method used in this study is a semi descriptive quantitative method. Where the purpose in this research is to explain the utilization of online financial applications as a medium for managing and managing finance. Online financial applications such as BukuKas, BukuWarung, FInansialku and also Money Lover proved very useful in managing or managing personal finances or individuals, families and also UMKM well, namely in terms of managing income, expenses, investments, receivables and financial statements. In addition, it is more effective and efficient also in terms of financial management time by using the online financial application.